Digital Innovations and Accident and Incident Control in Contractors (Journal SCIENCEVOLUTION, 2026)
The research was conducted at a supervisory company in Lima in 2024, within a context of growing need to improve occupational safety management for contractors. Its objective was to determine the influence of Behavior-Based Safety (BBS) digital innovations on accident and incident control. A quantitative, pre-experimental, applied methodology was employed. The sample consisted of accident and incident indicators recorded before and after the intervention. Data collection instruments included a digital innovations observation form for BBS and an accident and incident observation form. The results showed that, prior to implementation, the average control level was 15.8; the severity index, 230.3; and the accident rate, 4.9, with 193.4 incidents and 33.8 non-disabling accidents per month. Following the implementation of Smart OSH software, significant reductions were achieved: −69% in frequency, −78% in accident rate, and −91% in serious incidents. Student's t-test confirmed the statistical significance (p
Keywords: Digital Innovation; Behavior-Based Safety; Accident Control; Incident Control; Smart OSH; Occupational Safety; Contractors; Workplace Risk Management; Frequency Rate; Severity Rate